Host nest site choice depends on risk of cuckoo parasitism in magpie hosts. (30th August 2017) - Expósito-Granados, Mónica; Parejo, Deseada; Martínez, Juan Gabriel; Precioso, Marta; Molina-Morales, Mercedes; Avilés, Jesús M
Abstract : Studies on antiparasite defenses potentially operating prior to parasite egg deposition on cuckoo-host interactions are scarce in animal ecology. We experimentally assess the possibility that hosts, as part of a front-line defense, could diminish parasitism costs through informed nest-site choice based on visual and auditory cues informing on risk of cuckoo parasitism. Our results show that hosts can minimize the costs of cuckoo parasitism through informed nest-site choice Abstract: Avian brood parasites impose large fitness costs on their hosts and, thus, brood parasitism has selected for an array of host defensive mechanisms to avoid them. So far most studies have focused on antiparasite defenses operating at the egg and chick stages and neglected defenses that may work prior to parasite egg deposition. Here, we experimentally explore the possibility that hosts, as part of a front-line defense, might minimize parasitism costs through informed nest site choice based on perceived risk of cuckoo parasitism. We conducted a large-scale manipulation of visual and auditory cues potentially informing on the risk of great spotted cuckoo Clamator glandarius parasitism during the nest site choice period of the magpie Pica pica host to investigate its effect on host's nest settlement and individual year to year site fidelity. Early breeding magpies preferentially placed their nests in safe areas (i.e., in sites of low perceived risk of parasitism), and, this effect diluted with time elapsed since risk of parasitism was manipulated. Site fidelity of individual magpies decreased with risk of cuckoo parasitism, for those that were not parasitized in the previous year. Our results constitute the first strong evidence showing that hosts can minimize the costs of cuckoo parasitism through informed nest-site choice, calling for future consideration of defenses potentially operating prior to parasite egg deposition to achieve a better understanding of cuckoo-host coevolution.